2013
DOI: 10.1155/2013/931915
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cytokines and the Risk of Cardiovascular Complications in Type 2 Diabetes

Abstract: This study evaluates peripheral blood T lymphocyte expression of inflammatory and proinflammatory cytokines as well as T regulatory (Treg) (FOXP3+CD25+CD4+) cells in type 2 diabetes (T2DM). Participants included 40 T2DM and 30 healthy control subjects. Twenty-four patients had no complications while 16 were afflicted with coronary heart disease (CHD). Relative to healthy subjects, all T2DM patients showed a significant increase in expression of CD4+IFN-ϒ+, CD4+TNF-α+, and CD4+IL-8+ T cells (P < 0.001) as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 22 publications
(31 reference statements)
2
34
0
Order By: Relevance
“…It is well recognised that NF-κB transcriptional activity directly controls the main cytokine drivers of the Th1 response [7,47]. Furthermore, elevated levels of Th1 cytokines correlate with proteinuria [48] and the risk of cardiovascular complications [49] in patients with type 2 diabetes. Consistent with this, our findings indicate that regulation of the systemic Th1-mediated immunoinflammatory response may account, at least in part, for the in vivo protective effect of NBD in diabetic mice.…”
Section: Resultsmentioning
confidence: 99%
“…It is well recognised that NF-κB transcriptional activity directly controls the main cytokine drivers of the Th1 response [7,47]. Furthermore, elevated levels of Th1 cytokines correlate with proteinuria [48] and the risk of cardiovascular complications [49] in patients with type 2 diabetes. Consistent with this, our findings indicate that regulation of the systemic Th1-mediated immunoinflammatory response may account, at least in part, for the in vivo protective effect of NBD in diabetic mice.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in animal models as well as in humans have revealed that the expression of proinflammatory cytokines such as IL-6 and TGF-α is elevated and sustained by hyper glycemia [31,32] . An excessive inflammatory response has been accepted as a major contributing factor to periodontal tissue destruction and alveolar bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with DM are characterized by a state of chronic inflammation and abnormal activation of the innate immune system . Various inflammatory factors, such as monocyte chemoattractant protein‐1 (MCP‐1), tumor necrotic factor‐ α (TNF‐ α ), and C‐reactive protein (CRP) are upregulated in DM, and may play pivotal roles in the development of CVD in DM patients . Recently, gut microbiota were found to be related to obesity, metabolic endotoxemia, and low‐grade chronic inflammation .…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] Various inflammatory factors, such as monocyte chemoattractant protein-1 (MCP-1), tumor necrotic factor-α (TNF-α), and C-reactive protein (CRP) are upregulated in DM, and may play pivotal roles in the development of CVD in DM patients. [13][14][15][16] Recently, gut microbiota were found to be related to obesity, metabolic endotoxemia, and low-grade chronic inflammation. [17][18][19][20] Gut microbiota participate in the energy homeostasis of the host by modulating its capacity to harvest energy from given nutrients and in subsequent fat storage, 17 and can be modulated by dietary fiber, polysaccharides, or high-fat diets.…”
Section: Introductionmentioning
confidence: 99%